Accuracy of placement of ultrasound‐guided corticosteroid injection for subacromial pain (impingement) syndrome does not influence pain and function: Secondary analysis of a randomised controlled trial. (22nd March 2022) - Chean, Chung Shen; Raval, Parag; Ogollah, Reuben O.; Hall, Alison; Roddy, Edward; Foster, Nadine E.
Abstract: Objectives: To investigate whether the accuracy of placement of ultrasound‐guided (US‐guided) corticosteroid injections for subacromial pain (impingement) syndrome (SAPS) influences pain and function outcomes. Methods: This was a secondary analysis of data collected in a previous randomised controlled trial (RCT). Video images of US‐guided subacromial corticosteroid injections delivered in the RCT were reviewed to categorise injection accuracy into three groups: definitely/probably not in the subacromial bursa (Group 1); probably in the subacromial bursa (Group 2); and definitely in the subacromial bursa (Group 3). The primary outcome was the Shoulder Pain and Disability Index (SPADI) total score. Secondary outcomes included SPADI pain and function subscales and participants' self‐reported global impression of change. Outcomes were compared between the accuracy groups after adjusting for pre‐selected baseline characteristics. Results: US‐guided injection accuracy data were available for 114 participants: 22 categorised into Group 1, 21 into Group 2 and 71 into Group 3. There were no significant differences in mean total SPADI scores between the three injection accuracy groups at 6 weeks (Group 2 vs. 1: 8.22 (95% CI −4.01, 20.50); Group 3 versus 1: −0.57 (95% CI −10.27, 9.13) or 6 months (Group 2 vs. 1: 12.38 (95% CI −5.34, 30.10); Group 3 versus 1: 3.10 (95% CI −11.04, 17.23). Conclusions: The accuracy of injection placement in SAPS did not influence pain and function, suggesting that improvements in patients' outcomes using subacromial corticosteroid injections can be achieved without US guidance.